Sovereign soldiers : how the U.S. military transformed the global economy after World War II - Madsen, Grant (American business, politics, and society., 2018)
In Sovereign Soldiers, historian Grant Madsen tells the story of military leaders who took on an unfamiliar and often untold policymaking role during the occupation of Germany and Japan after World War II, applying a range of economic ideas whose impact would endure throughout the prosperous 1950s, including in the United States itself.